PEMANFAATAN PLATFORM MARKETPLACE UNTUK EKSPANSI BISNIS UMKM LOKAL - Fatmawati, Fatmawati; Khasanah, Siti Nur; Narti, Narti; Maruloh, Maruloh (Jurnal AbdiMas Nusa Mandiri, 2023)
The use of information technology in Gelam Jaya MSMEs has been used daily. However, restrictions on the use of information technology, especially the use of social media and marketplaces for business expansion, are still very passive.. Activity devotion to public this is very important remember the vital role of MSMEs in economy local. MSMEs often face challenge in promote product they in a way wide . Utilization of marketplace platforms can help local MSMEs to achieve more market share big , increase sales , and increase Power competitive they in the digital era. The purpose of activity This that is, to give training and support technical to local MSMEs so that they can leverage marketplace platforms to scale sale products and services they teach local MSMEs about importance digitalization in operate business them and give necessary skills in operate online . The activity method used in devotion This with method presentation material in a way direct with provide tutorials to participants . With held activity devotion public this is a local MSMEs can grow and develop , give contribution positive for the economy local , as well create impact positive social for owner business and society local. Activity This in line with efforts to strengthen Power MSME competitiveness in the digital era and promote economy local , sustainable.